The Effect of Compensation and Motivation on Employee Performance at PT. Telkom in Ternate City - Irwan, Nadira; Jabid, Abdullah W; Kamis, Ruslan A (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2024)
ABSTRACTObjective: This study aims to examine the effect of compensation and work motivation on employee performance at PT. Telkom, Ternate City. The research employs a quantitative approach to analyze the relationship between the independent variables (compensation and motivation) and the dependent variable (employee performance).Methodology: The research was conducted at PT. Telkom Ternate City branch, with the population comprising 151 employees. A census sampling technique was used, meaning that all employees were included in the study to ensure a comprehensive dataset. Primary data was gathered through questionnaires completed by the employees. Data analysis involved descriptive statistics, inferential statistics (including normality, multicollinearity, autocorrelation, and heteroscedasticity tests), multiple linear regression analysis, and hypothesis testing (F-test and t-test).Findings: The results of the study indicated that both compensation (t = 9.719, sig. = 0.000) and motivation (t = 3.162, sig. = 0.002) have a significant impact on employee performance at PT. Telkom, Ternate City, supporting the research hypothesis.Conclusion: This study underscores the significant influence of both compensation and work motivation on employee performance at PT. Telkom, Ternate City. The findings reveal that these factors contribute significantly to improving employee performance. To further enhance employee performance, PT. Telkom Ternate City should consider optimizing its compensation structure and motivation programs, which can lead to higher job satisfaction and organizational productivity.